Accountability and offsetting in environmental law enforcement. (14th February 2022) - NEHME, MARINA; PEDERSEN, OLE W.
Abstract: Since 2010, the Environment Agency of England has had a range of flexible tools at its disposal to deal with misconduct. One such sanction, enforcement undertaking, is akin to a settlement where the regulator and the offender agree to deal with the breach through a range of promises that may restore and remedy the environmental harm caused by the offence. The majority of these undertakings further require the offender to make donations to charitable environmental causes to improve the environment. However, there is little transparency around the latter promise. Consequently, this article details the findings of a pilot study interrogating the specific implementation of a subset of enforcement undertakings in the North East of England. The article argues that a more transparent enforcement process would address some of the accountability problems arising from the findings, which show that 'community benefits' operate as an offset mechanism instead of as a restorative enforcement mechanism.